Analisis Sistem Informasi Aplikasi Jasa Cuci Kendaraan Menggunakan Metode Waterfall - Bayu Pangestu; Irsad Fauzan (Journal of Information Systems and Business Technology, 2025)
Vehicle washing companies are among the many service sectors that are changing toward more organized and efficient procedures as a result of the development of digital technology. The purpose of this project is to use the Waterfall technique to assess and create a web-based vehicle wash service information system. Features like admin login, transactions, daily reporting, input validation, and service and customer data management are all included in the designed system. To make sure that system features work as intended by users, testing was done using the Black Box Testing approach. The outcomes demonstrate that all essential functions are operational, the system reacts to inputs precisely, and it gives suitable error feedback. The Waterfall technique facilitates documentation at every level by providing a methodical development structure. It has been demonstrated that this method speeds up service procedures, lowers record-keeping errors, and improves operational efficiency. To better satisfy consumer desires, additional development ideas include incorporating digital payment methods and including online booking capabilities. This method makes the web-based information system an appropriate way to help firms that provide car wash services go digital.